Availability, pricing, and affordability of antithrombotic medicines in Addis Ababa, Ethiopia: implications for health policy - Selam Birhanu; Melaku Tileku Tamiru; Hanan Muzeyin Kedir; Tamrat Assefa Tadesse (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Antithrombotic medications are essential for the management of abnormal clot formation. However, their availability, pricing, and affordability in Ethiopia, particularly in Addis Ababa, have not been comprehensively studied. Methods A cross-sectional study was conducted in Addis Ababa, Ethiopia to assess the availability, pricing, and affordability of essential antithrombotic medicines. This study utilized the World Health Organization (WHO) and International Health Action Organization methodology. Five public hospital outpatient pharmacies, four private hospitals, ten private pharmacies, four Kenema pharmacies, and two Red Cross pharmacies in Addis Ababa, Ethiopia, were included in the study. All essential antithrombotic medicines in the 6th edition of Ethiopia’s Essential Medicines List were included in this study. Data were collected for originator brands and the lowest-priced generic medicines available at each medicine outlet. Results The availability of low-priced generic (LPG) antithrombotic medicines was 31%, with private hospitals having the highest availability (52%). Original-brand antithrombotic medicines were rarely available, averaging only 3%, with private pharmacies showing a slightly higher availability (10%). The median price of LPG antithrombotic medicines is higher in private settings. Original-brand (OB) antithrombotic medicines in private hospitals and pharmacies were unaffordable, costing between 256.14 and 3,418 days of wages. Conclusion The availability of most antithrombotic medicines was low across all sectors compared with the WHO target. Private hospitals showed relatively higher availability of LPG medicines than other pharmacy outlets included in the study. There is a significant disparity between the availability and affordability of LPG and OB medicines. To address these issues, the national drug procurement and distribution systems must be strengthened. Exploring local production and financial assistance programs, implementing effective stock management, regulating medicine prices, promoting high-quality generic medicines, and conducting further research to understand the national landscape are all essential.